The autoimmune disease-associated KIF5A, CD226 and SH2B3 gene variants confer susceptibility for multiple sclerosis. - Alcina, Antonio; Vandenbroeck, Köen; Otaegui, David; Saiz, Alberto; González, José Ramón; Fernández Fernández, Óscar; Cavanillas, María L; Cénit, María C; Arroyo, Rafael; Alloza, Iraide; Garcia-Barcina, María; Antigüedad, Alfredo; et al. (Springer Nature, 2010)
Genome-wide association studies (GWAS) have revealed that different diseases share susceptibility variants. Twelve single- nucleotide polymorphisms (SNPs) previously associated with different immune-mediated diseases in GWAS were genotyped in a Caucasian Spanish population of 2864 multiple sclerosis (MS) patients and 2930 controls. Three SNPs were found to be associated with MS: rs1678542 in KIF5A (P= 0.001, odds ratio (OR) 1.13, 95% confidence interval (CI) 1.05–1.23); rs3184504 in SH2B3 (P= 0.00001, OR 1.19, 95% CI 1.10–1.27) and rs763361 in CD226 (P= 0.00007, OR 1.16, 95%CI 1.08–1.25). These variants have previously been associated with rheumatoid arthritis and type 1 diabetes. The SH2B3 polymorphism has additionally been associated with systemic lupus erythematosus. Our results, in addition to validating some of these loci as risk factors for MS, are consistent with shared genetic mechanisms underlying different immune-mediated diseases. These data may help to shape the contribution of each pathway to different disorders.
Keywords: Esclerosis múltiple; multiple sclerosis; rheumatoid arthritis; type 1 diabetes; KIF5A; CD226; SH2B3